Kolaborasi Kontekstual dengan PBL untuk Meninngkatkan Prestasi Belajar Matematika - fuad sofyan (LPPM IAI Hasanuddin Pare-Kediri, 2016)
The purpose of the study were: 1) To clarify the application of a contextual approach to the problem based on the subjects of Mathematics Unit of time, the unit of length and unit weight class IV-A State Elementary School Tunggangri Kalidawir Tulungagung. 2) To describe the improvement of student achievement through the implementation of a contextual approach to the problem based on the subjects of math class IV-A State Elementary School Tunggangri Kalidawir Tulungagung. Research results show that the application of problem-based contextual approach can improve learning achievement in Mathematics. This is evidenced by an increase in student achievement from the first cycle to the second cycle is the average value of learning outcomes at the end of the first cycle test was 68.79 (68.97%) were located on the criteria quite well, whereas at the end of the test cycle II was 81.93 (86.21%) and is at a good criteria. This shows an increase of 13.14. From these data it appears that the application of problem-based approach to improve the performance of contextual learning materials Mathematics units of time, length and weight class IV-A in the State Government Elementary School Tunggangri Kalidawir Tulungagung Academic Year 2013/2014.